Efficacy of Human Chorion Membrane Allograft for Recession Coverage: A Case Series. Issue 8 (1st August 2015) - Esteves, Janice; Bhat, K.M.; Thomas, Betsy; Varghese, Jothi M.; Jadhav, Tanya
Abstract : Background : Membranes of human placentas have been used in the field of medicine for skin grafts, treatment of burns, and ulcerated skin conditions with great success. The use of placenta allografts in dentistry is a more recent development, with the first commercial product being made available in 2008. The unique inherent biologic properties in placenta allografts enhance wound healing and may propagate regeneration. Methods: Ten healthy adult patients presenting with 21 Miller Class I gingival recession (GR) defects (isolated or adjacent multiple) were surgically treated with a modified coronally advanced flap and chorion membrane for root coverage. Clinical parameters measured at baseline, 3 months, and 6 months were probing depth, clinical attachment level, GR height, width of keratinized gingiva, and assessment of gingival biotype. Statistical analysis was performed to compare the treatment outcomes at the follow‐up intervals. Results: The results showed statistically significant ( P <0.001) improvements in all clinical parameters at the 3‐ and 6‐month follow‐ups. The mean percentage of root coverage at the end of 6 months was 89.92% ± 15.59%, and 14 of 21 treated GR defects showed 100% root coverage. The gingival biotype also showed a thick biotype in nine sites that had an initial thin biotype. Conclusions: Fetal membranes possess distinctive properties that can be harnessed to promote periodontal healing. The chorion membrane covered by a modified coronally advanced flap is a new approach that has shown promising results in terms of root coverage, increased width of keratinized tissue, and thickness of the gingival biotype.